USE OF AMINO ACIDS IN FRUIT AND PEEL OF GARLIC IN MEDICINE - Mamatkulova Ugilkhon; Isakov Hayotillo; Askarov Ibrokhim (Galaxy International Interdisciplinary Research Journal, 2022)
The article states that the synthesis of amino acids in the fruits and peel of garlic was determined by the method of Stephen A., Cohen Daviel, comparing the chemical composition of amino acids during processes in the human body. Provides information on the content of amino acids in fruits and peel of garlic